Correction: Molecular characterization and cuticular stomatal anatomy of Punica Granatum L. cultivars study in Dohuk governorate - Dalal Y. Kh. Sinjare; Shamiran S. Abdulrahman; Nizek S. Khalid; Rizgar Y. Ismail; Muhammad Yasir Naeem; Zeliha Selamoglu; Gani Issayev; Aveen M. N. Ahmed (Molecular Biology Reports, 2026)

Comparative Analysis of Polymeric and Lipid Polymer Hybrid Nanoparticles: In-Vitro and In-Vivo Analysis for Pulmonary Delivery of Atorvastatin - Kifayat Ullah Shah; Muhammad Usama Ghani Khan; Fahad Y. Sabei; Muhammad Danish Saeed; Firdous Ahmad Burki; Muhammad Yasir Ghani Khan; Awaji Y. Safhi; Ahmad Salawi; Abdullah Alsalhi; Ali Hanbashi (Journal of Pharmaceutical Innovation, 2026)

Inhibition of detoxification and antioxidant enzymes and expression fate of GSTe2 gene expression in Aedes aegypti larvae exposed to Azadirachta indica extract - Ihsan Ullah; Yasir Anwar; Tahseen Kamal; Muhammad Faisal Siddiqui; Mazhar Ul-Islam; Kavitha Thangavelu (South African Journal of Botany, 2026)

Phytochemical-rich extract of Psidium guajava ameliorates letrozole-induced PCOS in female rats by modulating the NF-κB inflammatory pathway - Hao Xu; Palwasha Haider; Majid Manzoor; Rida Siddique; Hina Manzoor; Muhammad Yasir Ali; Rizwan Rashid Bazmi; Liaqat Hussain; Ping Wang (Tissue and Cell, 2026)

Comprehensive analysis of rock-mud filtrate interactions at elevated temperatures: Implications for drilling and reservoir management in oil and gas industry - Imtiaz Ali; Maqsood Ahmad; Muhammad Yasir (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Toward sustainable mining: Experiment-based comparative investigation of energy absorption techniques for reducing air overpressure and enhancing rock fragmentation - Talib Hussain; Yasir Ahmad; Shahbaz Abbas; Afshan Naseem; Syed Tasweer Hussain Shah; Muhammad Zaka Emad (Engineering Geology, 2026)

Reusing end-of-life reverse osmosis membranes: Strategies, challenges, and future perspectives - Zeeshan Arshad; Muhammad Ashraf; Taha Demraoui; Tauqir Ahmad; Muhammad Bilal Asif; Niaz Ali Khan; Mukarram Zubair; Muhammad Irshad Baig; Nisar Ullah; Yasir Abbas; Almotasembellah Abushaban; Nadeem Baig (Desalination, 2026)

Climate-resilient livestock systems in Sub-Saharan Africa: a one health systems framework integrating pastoralism, animal health, and sustainable development - Muhammad Yasir Alhassan; Abdulhamid Abdullahi Ahmad; Mubarak Aliyu Danmaraya (Tropical Animal Health and Production, 2026)

Integrative mechanisms of photoperiod and temperature regulation in insect diapause - Dilawar Abbas; Kamran Haider; Farman Ullah; Muhammad Yasir Ali; Umer Liaqat; Maolin Hou (Journal of Pest Science, 2026)

Dose–response efficacy and safety of the aldosterone synthase inhibitor baxdrostat in resistant hypertension: a systematic review and network meta-analysis - Muhammad Shahzaib; Hafsa Ali; Muhammad Roshaan; Anza Muhammad; Muhammad Yasir; Muhammad Shahryar; Nimra Afzal; Eman Shahzad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Retraction notice to “Environmentally responsive and anti-bugs textile finishes – Recent trends, challenges, and future perspectives” [Sci. Total Environ. 690 (2019) 667–682] - Shahzad Ali Shahid Chatha; Muhammad Asgher; Rabbia Asgher; Abdullah Ijaz Hussain; Yasir Iqbal; Syed Makhdoom Hussain; Muhammad Bilal; Faizan Saleem; Hafiz M.N. Iqbal (Science of The Total Environment, 2026)

Ship-PFTracker: A robust ship tracking framework in short-time SAR imagery with particle filtering - Shanwei Liu; Ruikai Yu; Muhammad Yasir; Manuel A. Aguilar; Yuhan Kong; Shiqing Wei; Mingming Xu; Weimin Huang (Ocean Engineering, 2026)

Chitosan-crosslinked microwave-engineered biochar alleviates lead stress in Brassica napus by improving soil functioning and plant performance in Pb-contaminated soil - Fakhir Hannan; Yiwa Hu; Ahsan Ayyaz; Muhammad Iqbal; Muhammad Umair Yasin; Iram Batool; Juanjuan Li; Faisal Islam; Yasir Hamid; Muhammad Ahsan Farooq; Weijun Zhou (Journal of Environmental Management, 2026)

Ti-MOF anchored polyaniline network on separator: A dual-function strategy for polysulfide immobilization and redox enhancement in Li-S batteries - Abdul Majid Khan; Yasir Shah; Fakhar Zaman; Rashida Yahya; Safdar Abbas; Dianfa Zhao; Muhammad Usman Hameed; Wei Liu; Teng Zhang; Zhanpeng Wu (Fuel, 2026)

Multifunctional MXene film–embedded GFRP composites: Enabling EMI shielding and efficient electrothermal de-icing - Muhammad Yasir Khalid; Abdallah Kamal; Dawei Zhang; Lianxi Zheng; Kin Liao; Kamran Ahmed Khan; Rehan Umer (Chemical Engineering Journal, 2026)

Edaravone dexborneol in acute ischemic stroke: a systematic review and meta-analysis of randomized trials with clinical and thrombectomy-specific subgroup analyses - Eman Tariq; Hooriya Ahmed; Tayyaba Ikram Qazi; Abdul Muhaimin; Aleena Amir Malik; Javeria Soomro; Rahimeen Qureshi; Zainab Murtaza; Sarum Ali Khan; Wajeeha Komal; Hadia Tanveer; Rida Ameer; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Multifunctional Greenly Synthesized ZnFe2O4@ZnO Nanocomposites for Photodegradation of Azo Dyes and Antibacterial Applications: Effect of Radical Scavengers and Reaction Parameters - Muhammad Faizan; Muhammad Zahid Ishaque; Yasir Zaman; Abu Bakar Siddique; Muhammad Shahzad; Alia Arif; Hira Zaman (Water, Air, & Soil Pollution, 2026)

Inversion of Self-Potential Data from Regular Geometric Objects Using Bat Algorithms - Idrees Khan; Yi-an Cui; Muhammad Ishfaque; Syed Yasir Ali Shah (Pure and Applied Geophysics, 2026)

Theoretical Investigation of Optoelectronic and Photophysical Properties in the Carbazole-based Molecules via DFT and TD-DFT Methodology - Muhammad Zohaib Sabir; Sania Ismaeel; Yasir Ali; Aneeqa Kanwal; Umme Habibah Siddiqua (Journal of Fluorescence, 2026)

GCMS, phytochemical analysis, biological potential of dichloromethane extract of Yucca elephantipes regel roots: in vitro and in silico studies - Muhammad Shoaib Khan; Mehreen Jabeen; Farhan Siddique; Sajjad Ahmad; Amna Aqdas; Umair Jillani; Yasir Zaman; Abdulrahman Alshammari; Norah A. Albekairi (Natural Product Research, 2026)

An innovative minimum cost flow phase unwrapping algorithm based on compressive sensing for multi-temporal small baseline DInSAR interferograms sequences - Muhammad Yasir; Francesco Casu; Claudio De Luca; Giovanni Onorato; Riccardo Lanari; Michele Manunta (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Dynamic interaction of lorentz forces and arrhenius thermal kinetics in shear-thinning/thickening fluids through porous medium - S. Bilal; Asadullah; Muhammad Yasir (Dynamics of Atmospheres and Oceans, 2026)

Discovery and Functional Evaluation of Enterobacter gossypi sp. nov. (RT) for Salinity Stress Alleviation in Cotton - Abid Ullah; Aqsa Bibi; Ma Yonghui; Muhammad Atif Azeem; Ali Hazrat; Yasir Arafat; Caixia Han; Nigora Kuchkarova; Hua Shao (Journal of Soil Science and Plant Nutrition, 2026)

Host–Microbiota Metabolic Interactions in Atherosclerosis: Oral, gut, and Blood Perspectives - Ikram Khan; Muhammad Irfan; Ali Sher Bacha; Imran Khan; Yasir Ali; Zhiqiang Li (Probiotics and Antimicrobial Proteins, 2026)

An attempt at underwater image lightweight super-resolution using transformer and frequency-domain learning - Haoran Wu; Haitao Wang; Yifan Zhang; Muhammad Yasir Faheem; Xinghua Wang (Frontiers in Marine Science, 2026)
Lightweight image Super-resolution (SR) is a computer vision technology that aims to recover high-quality image details from low-resolution images with limited computing costs. While Transformer-based SR models have made remarkable advancements, their balanced edge-end deployment and reconstruction quality have been notably hindered by complex underwater imaging conditions and the scarcity of publicly available high-quality datasets. To address these issues, we propose a Frequency-domain Learning Transformer (FLT) for underwater images SR, which leverages complementary information from spatial and frequency domains to enable fine-grained detail reconstruction while reducing storage and computing costs. Specifically, FLT comprises Residual Dual-domain Joint Learning Transformer Blocks (RDTBs). Each RDTB captures low-frequency structures via the spatial-domain branch and high-frequency textures via the frequency-domain branch, thereby enhancing fine-grained details of lightweight SR. Furthermore, a Multi-scale FeedForward Neural (Ms-FFN) network is incorporated into each RDTB as an auxiliary detail enhancement module, which improves the visual fidelity of reconstructed images through multi-scale feature aggregation. We perform visual and quantitative comparisons, ablation studies, and model analyses against state-of-the-art methods on both the public UFO-120 dataset and the KLSG-II dataset. Experimental results demonstrate that FLT achieves performance comparable to or exceeding state-of-the-art SR models, while having significantly reduced by about 50% to 60% parameters and drastically reduced computational cost. This unique balance between reconstruction quality and efficiency underscores FLT’s superiority for lightweight underwater SR, providing a promising solution for resource-constrained underwater imaging applications. The code is available at https://github.com/WanghtCC/FLT .

SegTS: Subseries-driven temporo-spatial learning with Segment Anything Model for crop segmentation in satellite image time series - Jinsong Li; Tao Zhang; Shiqing Wei; Shujun Zhang; Mingming Xu; Muhammad Yasir; Shanwei Liu (Computers and Electronics in Agriculture, 2026)

Experimental study on optimizing explosive energy distribution for a cost-effective solution to minimize blasting hazard and improve rock fragmentation - Talib Hussain; Yasir Ahmad; Shahbaz Abbas; Syed Tasweer Hussain Shah; Afshan Naseem; Muhammad Zaka Emad (Bulletin of Engineering Geology and the Environment, 2026)

Fiber type-specific expression of LACTB leverages a function in oxidative metabolism - Kirsi-Marja Alanen; Rabah Soliymani; Jaakko Sarparanta; Satu Kuure; Kirsi Sainio; Zydrune Polianskyte; Muhammad Yasir Asghar; Ehsan Zangene; Annunziata Cascone; Maciej Lalowski; Peter Hackman; Johan Lundin; et al. (Histochemistry and Cell Biology, 2026)
Skeletal muscle is composed of type I and type II fibers, each characterized by specific metabolic machinery. LACTB is a conserved mitochondrial protein implicated in lipid utilization and tumorigenesis, but its precise function in the cellular metabolism remains unclear. To gain novel insight into the functional role of LACTB, we investigated skeletal muscle to determine whether LACTB is segregated by fiber type. The expression of LACTB was determined by immunohistochemistry (IHC) and immunoblotting in skeletal muscle from healthy human subjects and the laboratory rat. The specificity of the antibody was assessed using recombinant human LACTB protein and endogenous LACTB in isolated mitochondria. IHC results were validated in a cellular model of myoblast differentiation using the C2C12 and L6 cell lines. The results demonstrated that LACTB is highly enriched in adult type I muscle fibers. During development, LACTB expression commences in type I primary myotubes at the time of their formation around week 20 of gestational age. LACTB expression in myoblasts is low but increases rapidly upon the induction of myotube differentiation. We conclude that LACTB plays a distinct role in mitochondria of type I fibers, most likely acting in oxidative metabolism related to energy use from lipids. This defines LACTB as a mitochondrial marker for type I fibers.

Review on flexible frameworks: Phosphazene functional polymers powering the future of membranes - Yasir Abbas; Muhammad Waqar Hameed; Zahid Ali; Ghulam Yasin; Kanwal Shabbir; Ijaz Hussain; Muhammad Ahsan Iqbal; Hafiz M. Adeel Sharif; Zhanpeng Wu; Nadeem Baig; Isam H. Aljundi; Niaz Ali Khan; et al. (Chemical Engineering Journal, 2026)

Veterinary antimicrobial resistance as a climate-sensitive emerging infectious disease: a paradigm shift in one health surveillance - Muhammad Yasir Alhassan (Veterinary Research Communications, 2026)

Zinc oxide nano-priming fortifies Triticum aestivum L. against salt stress through physio-morphological, biochemical and transcriptomic responses - Muhammad Ateeq; Muhammad Azeem Ashraf; Qingfeng Dong; Hao Ren; Tauqeer Ahmad Yasir; Linzhou Huang; Liang Chen; Yin-Gang Hu (Plant and Soil, 2026)

Integrated physicomechanical, petrographic, and geochemical evaluation of eocene carbonate aggregates from the Salt Range, Pakistan - Khawaja Shoaib Ahmed; Muhammad Basharat; Amir Shahzad; Yasir Sirfraz; Muhammad Tayyib Riaz; Usama Shabir Abbasi; Salman Rasheed (Innovative Infrastructure Solutions, 2026)

Integrated Mechanical–NDT Evaluation of Moisture- and Weathering-Induced Weakening in Granite, Marble, and Limestone Joints - Waqas Ahmed; Azhar Ali; Abdul Rahim Asif; M. E. Al-Atroush; Muhammad Yasir (Rock Mechanics and Rock Engineering, 2026)

SSGNet: A single-source generalization model for ship detection in UAV imagery under challenging maritime environments - Muhammad Yasir; Shanwei Liu; Mingming Xu; Hui Sheng; Fernando J. Aguilar; Ranyeri do Lago Rocha; Felipe A.P. de Figueiredo; Arife Tugsan Isiacik Colak; Md Sakaouth Hossain (Ocean Engineering, 2026)

Biochar pyrolysis temperature determines the efficacy of 3, 4-dimethylpyrazole phosphate (DMPP) in reducing N2O emissions from low cadmium-contaminated paddy soil - Muhammad Laeeq Ur Rehman HASHMI; Muhammad Zia Ur Rahman HASHMI; Yasir HAMID; Bilal HUSSAIN; Tang SHENG; Wenjie LIU; Adnan ARSHAD; Tingqiang LI (Pedosphere, 2026)

Engineering active sites in binary PrCoO3/Mn2V2O7 heterointerface embedded in phosphorus-doped biochar for boosting pH universal water splitting - Sidra Aslam; Muhammad Safdar; Misbah Mirza; Yasir Abbas; Waseem Abbas; Basharat Ali (Fuel, 2026)

Characterizing global air pollution seasonality and trends through integrated satellite and meteorological analytics - Muhammad Naveed; Zulqarnain Satti; Muhammad Mateen Tahir; Qazi Muhammad Yasir; Hui Li; Faming Wang (Environmental Pollution, 2026)

Extended-spectrum beta-lactamase-producing Escherichia coli in dromedary camels: antimicrobial resistance in arid and semi-arid tropical regions - Muhammad Yasir Alhassan; Farida Abubakar; Abdulrahman Lawal (Tropical Animal Health and Production, 2026)

Quercetin as a promising HIS-C inhibitor and novel therapeutic against antibacterial drug-resistant Acinetobacter baumannii: in vitro and in silico insights - Mohammed Salleh M. Ardawi; Samar A. Badreddine; Muhammad Yasir; Safaa A. Turkistani; Ahmed Afandi; Abdulaziz A. Kimawi; Samah O. Noor; Adhari Alselmi; Salma Mohammed Alsayed; Mada S. Alharthi; Vivek Dhar Dwivedi; Pradeep Sharma; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Reservoir characterization for hydrocarbon assessment of Eocene carbonates in Meyal area, Potwar Plateau, Pakistan: implications from geophysical logs data - Yasir Hamid; Muhammad Kamran; Syed Mamoon Siyar; Saqib Mehmood; Taqweem Ul Haq Ali; Fayaz Ali; Ibrar Ul Haq; Izhar Ullah; Kamran Shams; Sartaj Husain (Carbonates and Evaporites, 2026)

Lignite as a multifunctional additive to enhance methanogenesis and digestate humification in anaerobic digestion via facilitated electron transfer - Kaijun Wang; Yasir Abbas; Muhammad Saqlain Jamil; Fayyaz Ali Shah; Linxuan Li; Pei Liang; Xingpeng Jing; Litong Ma; Weihuang Zhu; Sining Yun (Journal of Cleaner Production, 2026)

Fe-and Mg-functionalized chicken manure biochar immobilized Cd, Cr, and Pb in aged soil and decreased their leaching into groundwater - Yasir Hamid; Qiang Lin; Muhammad Saqib Rashid; Muhammad Usman; Yonglong Chen; Esmat F. Ali; Hamada Abdelrahman; Temoor Ahmed; Sabry M. Shaheen; Sang Soo Lee; Xiaoe Yang (Groundwater for Sustainable Development, 2026)

El Niño-Southern Oscillation-driven variability in drought severity across the Upper Indus Basin, Pakistan - Yasir Latif; Muhammad Yaseen (Theoretical and Applied Climatology, 2026)

Phosphorene based nano-sensors for mycotoxins in food products: a review - Bilal Afzal; Nuzhat Jamil; Khadija Gull; Muhammad Yasir; Qudsia Kanwal; Toheed Ahmed; Attaullah Bukhari (Mycotoxin Research, 2026)

Sodium carbonate and sodium chloride as elicitors of secondary metabolite production in callus cultures of Fagonia indica - Muhammad Uzair Javed; Muhammad Asad Ullah; Tehreem Mahmood; Taimoor Khan; Iva Viehmannova; Anmol Akbar; Yasir Khan; Tariq Khan; Bilal Haider Abbasi; Christophe Hano; Nathalie Giglioli-Guivarc’h (Plant Biosystems, 2026)

A multi-source framework for shallow landslide detection and warning in Da-river basin, Vietnam - Hieu Nguyen; Kinh Bac Dang; Minh Hieu Nguyen; Trong Huong Nguyen; Thi Phuong Nga Pham; Thi Ngan Do; Muhammad Yasir; Van Bao Dang (International Journal of Remote Sensing, 2026)

Southward to northward shifting trends of monsoonal precipitation and their connections with atmospheric circulations over Pakistan: A comparative study of 1961–1990 and 1991–2020 - Sohail Abbas; Amina Ameer; Fenglin Lv; Tingting Li; Yi Chen; Liang Cao; Heli Lu; Yasir Latif; Muhammad Yaseen; Siqi Lu; Wanfu Feng; Amjad Ali Khan (Journal of Hydrology, 2026)

Isolation, Characterization, and Modes of Action of Antifungal Compounds from Rhizomes of Dryopteris nigropaleacea - Faisal I. Jafri; Muhammad Akbar; Yasir Nazir; Amna Khalil; Khizar H. Bhatti; Anna Andolfi; Muhammad W. Mazhar; Shoaib Ashiq (Current Microbiology, 2026)

Investigating the Wound Healing Potential of CuCO3 Nanoparticles in Alloxan-Induced Diabetic Albino Mice: An Experimental and In Silico Approach - Muhammad Saqib Rafiq; Jabbir Ali Khan; Ashfaq Ahmad Shah Bukhari; Samra Shafqat; Ahmad Waheed; Muhammad Yasir Abbas; Muhammad Waseem Aslam; Imran Ibrahim Shaikh; Khalid S. Almaary; Muhammad Saleem Khan (Biological Trace Element Research, 2025)

Transition of the Karakoram anomaly under emerging hydroclimatic trends - Yasir Latif; Sara C. Pryor; Sardar Ateeq-Ur-Rehman; Sher Muhammad; Muhammad Yaseen; Muhammad Atif Wazir (Science of The Total Environment, 2025)

Transformation of wet chemically derived ZnGa-LDH to ZnO:GaN nano-alloys for PMS activated wastewater remediation - Yasir Abbas; Kanwal Shabbir; Haider Aziz; Ijaz Hussain; Hafiz M. Adeel Sharif; Muhammad Ahsan Iqbal; Majid Basharat; Haoliang Wang; Niaz Ali Khan (Journal of Environmental Chemical Engineering, 2025)

First comprehensive phenolic profiling and antioxidant assessment of red seaweed (Mazzaella japonica) using cold plasma-treated water - Abul Hossain; Muhammad Yasir; Yigong Guo; Anika Singh; David D. Kitts; Anubhav Pratap-Singh (Food Chemistry, 2025)

Influence of Cattaneo-Christov radiative heat flux in magnetized flow performance of three different materials with variable constraints - Muhammad Yasir; Karim Choubani; Muhammad Naveed Khan; Mohammed A. Almeshaal; Mohamed Hussien (Dynamics of Atmospheres and Oceans, 2025)

One-pot Facile Synthesis of Polyhexahydrotriazine and Investigating its Application for Removal of N-Nitrosodiphenylamine from Wastewater - Yasir Abbas; Muhammad Sajid; Durga Rao Gijjapu; Mazen K. Nazal (Water, Air, & Soil Pollution, 2025)

Molecular characterization and cuticular stomatal anatomy of Punica Granatum L. cultivars study in Dohuk governorate - Dalal Y. Kh. Sinjare; Shamiran S. Abdulrahman; Nizek S. Khalid; Rizgar Y. Ismail; Muhammad Yasir Naeem; Zeliha Selamoglu; Gani Issayev; Aveen M. N. Ahmed (Molecular Biology Reports, 2025)

A machine learning assisted approach to classify rose species and varieties with laser induced breakdown spectroscopy - Maryam Manzoor; Muhammad Faheem; Muhammad Nadeem; Guljan Shreen; Faisal Hayat; Adnan Younis; Yasir Jamil (Analytica Chimica Acta, 2025)

Optimizing the anticancer action and toxicity evaluation of cobalt ferrite nanoparticles by different polyethylene glycol concentrations - Kanwal Akhtar; Muhammad Khawar Abbas; Nida Muzammil; Naveed Akhtar Shad; Qaisar Iqbal; Wasim Abbas; Faqir Muhammad; Bushra Akhtar; Yasir Javed; Habiba Khadim; Anam Munawar (Journal of Trace Elements in Medicine and Biology, 2025)

Photo-responsive halogen-doped carbon quantum dots enhance anaerobic co-digestion: Focusing on biogas yield and electron transfer - Cheng Peng; Sining Yun; Kaijun Wang; Yangyang Gao; Yasir Abbas; Han Luo; Muhammad Saqlain Jamil; Linxuan Li; Pei Liang (Journal of Cleaner Production, 2025)

Magnetic biochar for the remediation of arsenic contaminated water: A complete guide of science, synthesis, and solutions - Yasir Hamid; Yonglong Chen; Muhammad Haris; Muhammad Usman; Bilal Hussain; Muhammad Saqib Rashid; Temoor Ahmed; Muhammad Noman; Xiaoe Yang (Journal of Environmental Chemical Engineering, 2025)

Retraction notice to “Sustainable, economical and rapid treatment of multiple lung diseases using therapeutic potential of curcumin nanoparticles” [Environ. Res. 233 (2023) 116477] - Qudsia Kanwal; Samiah Shahid; Abeel Ahmad; Arif Nazir; Muhammad Yasir; Aneela Anwar; Samar Z. Alshawwa; Munawar Iqbal (Environmental Research, 2025)

Unraveling the Biology and Integrated Management Strategies for Tobacco Beetle (Lasioderma serricorne) in Stored Tobacco: A Comprehensive Review - Ayesha Younas; Muhammad Adnan Bodlah; Yasir Niaz; Alishbah Mohsin; Aleena Kanwal; Imran Bodlah (Journal of Crop Health, 2025)

Variation in Ectotherm Thermal Tolerances With Elevation and Temperature Across Biological Scales - Imran Khaliq; Edward Lavender; Haseeb Kamran; Muhammad Junaid Shahid; Muhammad Sheraz; Muhammad Awais; Mehtab Shabir; Muhammad Yasir; Abdul Hameed; Muhammad Asgher; Abdul Rehman; Maria Riaz; et al. (Global Ecology and Biogeography, 2025)
Aim Variation in thermal tolerances along environmental gradients is assumed to follow similar patterns across different biological scales, including within and between species, and across communities. However, this assumption has yet to be tested using comprehensive datasets collected through standardised methodologies. Location Southern Asia. Time Period 2017–2019. Major Taxa Studied Ants, beetles, grasshoppers, and spiders. Methods We quantified the associations between thermal tolerance traits and elevation or temperature at three biological scales (community, broad taxonomic group, and species) along two distinct elevational transects in Southern Asia. In total, we measured thermal tolerances of over 15,000 individuals from 114 arthropod species belonging to four invertebrate taxa (ants, beetles, grasshoppers, and spiders). We compared the relationships at each scale using mixed‐effects models. Results At the community scale, across all individuals of all species, we found a consistent decline in the values of three thermal tolerance traits (upper tolerance, lower tolerance, and tolerance breadth) with elevation along the Himalayan transect but an increase in the values of upper and lower tolerance along the Sulaiman transect. The relationships of thermal tolerance traits and elevation/temperature varied among the groups and species between the Himalayan and Sulaiman transects. This suggests that factors beyond elevation, including vegetation composition, microclimate, landscape features, and local adaptation, drive observed variation in thermal tolerance traits among and within species. Conclusion Our study highlights the interplay between thermal physiology and the environment across different habitats and biological scales. Our findings indicate that predicting biodiversity responses to environmental change based on thermal tolerance–environment relationships requires careful consideration of group‐ and species‐level variation. This is essential for improving the accuracy of climate change impact assessments on biodiversity.

Editorial: Remote sensing applications in oceanography with deep learning - Muhammad Yasir; Chao Chen; Shah Nazir; Weimin Huang (Frontiers in Marine Science, 2025)

Circular RNAs: Diversity, formation, functions, and identification mechanism with a focus on endogenous circular RNAs - Muhammad Umer; Naureen Anwar; Mustansar Mubeen; Yasir Iftikhar; Manoj Kumar Solanki; Muhammad Ahmad Zeshan; Khalid M. Alsyaad; Yun Li; Pingwu Liu (Physiological and Molecular Plant Pathology, 2025)

A comprehensive review on the recovery of lithium from lithium-ion batteries and spodumene - Asad Ali; Sadia Afrin; Abdul Hannan Asif; Yasir Arafat; Muhammad Rizwan Azhar (Journal of Environmental Management, 2025)

Advancing environmental sustainability through enhanced enterprise resource planning and green supply chain integration: Evidence from the manufacturing sector - Weiqiong Fu; Tahir Ali; Yasir Hussain; Muhammad Asif (Journal of Environmental Management, 2025)

Geothermal investigation of sandstone reservoirs using a probabilistic neural network with 2D seismic and borehole data: insights into structural and reservoir characteristics - Zohaib Naseer; Muhsan Ehsan; Muhammad Ali; Kamal Abdelrahman; Yasir Bashir (Geothermics, 2025)

The miRNA-based liquid biopsies for environmental health risk assessment: Insights into arsenic-induced hepatotoxicity and systemic health impacts - Muhammad Yasir Abdur Rehman; Marcel van Herwijnen; Riffat Naseem Malik; Jacco Jan Briedé; Julian Krauskopf (Science of The Total Environment, 2025)

Multi-scale vessel trajectory clustering: An adaptive DBSCAN method for maritime areas of diverse extents - Hui Sheng; Zheao Huang; Ling Ke; Julin Zhang; Zhe Zeng; Muhammad Yasir; Shanwei Liu (Ocean Engineering, 2025)

Boosted wound healing and anticancer potential of polymer functionalized cerium oxide nanomaterials - Muhammad Khawar Abbas; Yasir Javed; Naveed Akhtar Shad; Azhar Rasul; Amna Bashir; Syed Fazil Bin Farukh; Heba Taha Abdulghani; Wasim Abbas; Aisha Sethi; Muhammad Ramzan Khawar; Dongwhi Choi (Journal of Trace Elements in Medicine and Biology, 2025)

Global decline of aquatic and terrestrial insects driven by climate change and anthropogenic impacts: The interaction of multiple stressors and disruption of niche conservatism - Muhammad Farooq; Umair Khan; Muhammad Adnan; Waqar Younas; Nimra Bashir Qureshi; Qazi Muhammad Yasir; Qinghua Cai; Ming-Chih Chiu (Biological Conservation, 2025)

Adsorptive Remediation of Cadmium Ions with Modified Plant Straw Using Response Surface Methodology - Aanisa Manzoor Shah; Inayat Mustafa Khan; Rehana Rasool; Tahir A. Sheikh; Muhammad Athar Khaliq; Shaista Nazir; Javid A. Bhat; Yasir Hanif Mir; Rifat un Nissa; Sami Al Obaid; Mohammad Javed Ansari; Shafeeq Ur Rahman (International Journal of Environmental Research, 2025)

Molecular modeling to design a multiepitope vaccine against emerging tick-borne Yezo virus and its validation through biophysics techniques - Hassan Ayaz; Muhammad Suleman; Asad Ali Shah; Syed Ainul Abideen; Faisal Ahmad; Muhammad Ali; Sajjad Ahmad; Asia Nawaz; Hanbal Ahmad khan; Inam Hussain; Muhammad Irfan; Yasir Waheed (In Silico Pharmacology, 2025)

Untargeted UHPLC-Q exactive orbitrap HRMS-based network pharmacology for the discovery of anti-breast cancer compounds from spatholobus littoralis stems fractions and experimental validation - Tedi Rustandi; Muhammad Riko Nugroho; Muhammad Yasir; Kamalia; Elza Julian Eka Putri Nugraha; Muhammad Hafizh Abiyyu Fathin Fawwazi; Senya Puteri Amalia; Abdul Mahmud Yumassik; Farida Hayati; Ahmed Mahal; Ahmad J. Obaidullah (Natural Product Research, 2025)

Machine learning approach for photocatalysis: An experimentally validated case study of photocatalytic dye degradation - Hassan Ali; Muhammad Yasir; Hamza Ul Haq; Ali Can Guler; Milan Masar; Muhammad Nouman Aslam Khan; Michal Machovsky; Vladimir Sedlarik; Ivo Kuritka (Journal of Environmental Management, 2025)

Solvothermal synthesis of ruthenium doped MnV2O7@g-C3N4 nanocomposite for oxygen evolution reaction and high-performance asymmetric supercapacitors - Sidra Aslam; Muhammad Safdar; Sadia Akram; Muhammad Awais; Basharat Ali; Yasir Abbas; Waseem Abbas; Misbah Mirza (Journal of Environmental Chemical Engineering, 2025)

Rapid and selective E-waste gold extraction from aqua regia by dual redox active-sites of skeleton modulated poly(organo)phosphazenes - Yasir Abbas; Sajjad Ali; Majid Basharat; Hafiz M. Adeel Sharif; Muhammad Ahsan Iqbal; Mohamed Bououdina; Haoliang Wang; Niaz Ali Khan (Chemical Engineering Journal, 2025)

Carissa macrocarpa Extract Based Greenly Synthesized AuNPs: A Sustainable Approach for Lead Ion Detection, Azo Dye Degradation, and Antimicrobial Applications - Abu Bakar Siddique; Muhammad Ashraf Shaheen; Azhar Abbas; Yasir Zaman; Mamoon Ur Rasheed; Abdul Karim; Muhammad Mustaqeem; Muhammad Fayyaz ur Rehman; Mohammad Mahtab Alam; Amirah S. Alahmari (Water, Air, & Soil Pollution, 2025)

QTL Mapping and Candidate Gene Analysis for Wax Trait of Stem and Leaf in Durum Wheat (Triticum turgidum L. ssp. durum (Desf.)) - Yijing Cai; Yasir Muhammad; Yujie Zhou; Yuefen Cao; Junkang Rong; Xin Hu (Plant Molecular Biology Reporter, 2025)

Hydrocarbon generation potential of the lower Jurassic-Eocene intervals in the Potwar Plateau, Pakistan: insights from organic geochemical, 1D basin modeling and petrographic analysis - Masood Shah; Syed Mamoon Siyar; Abbas F. Gharib; Iman M. Anwer; Muhammad Irfan; Mohammad Salman Shamim; Nasar Khan; Taqweem Ul. Haq; Yasir Hamid; Kamran Shams (Carbonates and Evaporites, 2025)

Transgenerational Impact of nicotiana tabacum extract on musca domestica (diptera: muscidae) - Muhammad Jamshed Iqbal; Zhihang Zhuo; Inzamam Ul Haq; Yasir Niaz; Basharat Ali; Ammara Riaz; Habib Ali; Rashid Iqbal; Gadah Albasher; Mohammad Javed Ansari (International Journal of Tropical Insect Science, 2025)

Unveiling the Microplastics Menace in Freshwater Fishes: Evidence from the Panjnad Barrage, South Punjab, Pakistan - Syed Muhammad Moeen Uddin Raheel; Adnan Ahmad Qazi; Muhammad Latif; Huma Naz; Yasir Waqas; Maximilian Lackner (Fishes, 2025)
This study explored the prevalence and types of microplastic (MP) pollution in three fish species—Labeo rohita, Wallago attu, and Cirrhinus mrigala—collected from the Panjnad Barrage in South Punjab, Pakistan. MPs were analyzed from the gastrointestinal tracts (GITs), gills, and muscles of 90 fish samples. Advanced analytical techniques, including Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy/Energy-Dispersive X-Ray Spectroscopy (SEM/EDX), and Gas Chromatography/Mass Spectrometry (GC/MS), were deployed, confirming the polymeric composition and presence of various additives. Quantitative and qualitative analyses revealed significant variations in MP accumulation across tissues, with the GIT consistently showing the highest MP count, the gills having the highest concentration per gram, and the muscles exhibiting the lowest amount of accumulation. Wallago attu was found to have accumulated the highest concentration of microparticles among all three species due to its feeding habits and habitat. Fibers and fragments were the predominant types of MPs, with yellow and red being the most frequent colors. Polypropylene (PP) and polyethylene (PE) were the primary polymers identified, alongside other types like polyethylene terephthalate (PET) and polyvinyl chloride (PVC). The MP size distribution indicated that mid-sized particles (150–50 µm) were most abundant in the GIT and gills, while smaller particles (

Diffused sunlight assisted green synthesis of silver nanoparticles using Cotoneaster nummularia polar extract for antimicrobial and wound healing applications - Nasir Assad; Muhammad Naeem-ul-Hassan; Muhammad Ajaz Hussain; Azhar Abbas; Muhammad Sher; Gulzar Muhammad; Yasir Assad; Muhammad Farid-ul-Haq (Natural Product Research, 2025)

Delving Into Nanoparticle Systems for Enhanced Drug Delivery Technologies - Nimra Abaidullah; Khalid Muhammad; Yasir Waheed (AAPS PharmSciTech, 2025)

Phosphorus Application Improved Grain Yield, Phosphorus Use Efficiency and Economic Returns of Different Pearl Millet Genotypes Grown on Alkaline Soil - Abdul Majeed; Muhammad Bahram Khan; Ahmad Dawood; Yasir Mehmood; Sami Ul-Allah; Mubshar Hussain (Journal of Soil Science and Plant Nutrition, 2025)

Unraveling insect feeding patterns and their ecological impacts on plant defense mechanisms - Arzlan Abbas; Muhammad Zulqar Nain Dara; Farman Ullah; Babu Saddam; Sohail Abbas; Aleena Alam; Mobeen Babar; Faisal Hafeez; Muhammad Dildar Gogi; Hamed A. Ghramh; Khalid Ali Khan; Yasir Niaz; et al. (Journal of Plant Diseases and Protection, 2025)

Insight into insecticide resistance mechanism and eco-friendly approaches for the management of olive fruit fly, Bactrocera oleae Rossi: a review - Ansa Majeed; Muhammad Tariq Rasheed; Javairia Akram; Noreen Shahzadi; Mehvish Kousar; Imran Bodlah; Javaid Iqbal; Inzamam Ul Haq; Yasir Munir; Junaid Ali Siddiqui (Journal of Plant Diseases and Protection, 2025)

A novel (−)-(2S)-7,4′-dihydroxyflavanone compound for treating age-related diabetes mellitus through immunoinformatics-guided activation of CISD3 - Abdur-Rehman Munir; Saad Ilyas Baig; Muhammad Asif Razzaq; Fatima Rauf; Yasir Ali; Syed Muhammad Abdullah Azam (Biogerontology, 2025)

Modelling the relationship between industrial air pollution and perceived health effects of households in the three most air-polluted cities of Pakistan - Yasir Mehmood; Muhammad Arshad (Environmental Monitoring and Assessment, 2025)

A multi-proxy approach to explore paleoenvironmental oscillations and chronostratigraphy of Thanetian carbonates in Eastern Tethys, Pakistan - Amir Shahzad; Yasir Sirfraz; Khawaja Shoaib Ahmed; Muhammad Hanif; Muhammad Tayyib Riaz; Khawaja Shafique Ahmad; Thierry Adatte (Marine and Petroleum Geology, 2025)

Coal thermal power plant magnetic fly ash as an accelerant for anaerobic digestion of cow dung and aloe peel residue: Optimizing the particle size under static magnetic field - Yasir Abbas; Sining Yun; Kaijun Wang; Muhammad Saqlain Jamil; Xiaomin Zhang; Cheng Peng; Han Luo (Chemical Engineering Journal, 2025)

Impacts of natural and anthropogenic changes on the morphology and shoreline dynamics along the southeast coast of Bangladesh - Md Sakaouth Hossain; Muhammad Yasir; Zahidul Bari; Mahmuda Khatun; Maftuha Jahan (Arabian Journal of Geosciences, 2025)

A systematic investigation of multi-attributive border approximation area comparison approach with Gaussian membership function for optimizing water quality - Yasir Yasin; Gulay Demir; Muhammad Riaz; Muhammad Aslam; Dragan Pamucar (Environment, Development and Sustainability, 2024)

Investigation of NO formation in non-premixed, swirl-stabilised, wet hydrogen/air gas turbine combustor - Rahul Palulli; Kai Zhang; Simeon Dybe; Muhammad Yasir; Christian Oliver Paschereit; Christophe Duwig (Fuel, 2024)

Successful application of modified crude DNA extraction from muscle tissues for various types of PCR amplifications - Sana Jafar; Salman Jamil; Muhammad Sheraz Yasin; Asif Naseem; Muhammad Yasir Zahoor; Wasim Shehzad; Muhammad Imran (Molecular Biology Reports, 2024)

Characterization and expression analysis of GLABRA3 (GL3) genes in cotton: insights into trichome development and hormonal regulation - Naisi Wu; Benyi Lu; YaSir Muhammad; Yaofen Cao; Junkang Rong (Molecular Biology Reports, 2024)

Development and validation of a universal primer pair for the taxonomic and phylogenetic studies of vertebrates - Sana Jafar; Khalid Mahmood Anjum; Muhammad Yasir Zahoor; Wasim Shehzad; Asif Naseem; Muhammad Imran (Molecular Biology Reports, 2024)

The GaKAN2, a KANADI transcription factor, modulates stem trichomes in Gossypium arboreum - Xujiao Ren; Luying Yang; Yasir Muhammad; Yuxing Xie; Xinyi Lin; Li Yu; Yuefen Cao; Mingquan Ding; Yurong Jiang; Junkang Rong (Molecular Genetics and Genomics, 2024)

Innovative strategies for characterizing and managing huanglongbing in citrus - Mustansar Mubeen; Amjad Ali; Yasir Iftikhar; Muhammad Shahbaz; Muhammad Irfan Ullah; Md. Arshad Ali; Noor Fatima; Jaya Seelan Sathiya Seelan; Yee Shin Tan; Uthman Balgith Algopishi (World Journal of Microbiology and Biotechnology, 2024)

Failure mechanism of a massive fault–controlled rainfall–triggered landslide in northern Pakistan - Muhammad Tayyib Riaz; Muhammad Basharat; Khawaja Shoaib Ahmed; Yasir Sirfraz; Amir Shahzad; Nisar Ali Shah (Landslides, 2024)

Immunoinformatic-based drug design utilizing hesperetin to target CISD2 activation for liver aging in humans - Saad Ilyas Baig; Maria Naseer; Abdur-Rehman Munir; Yasir Ali; Muhammad Asif Razzaq (Biogerontology, 2024)

Anelosimus eximius bioinspired ZnO nano cobwebs for environmental remediation of drugs and endocrine disruptors from water - Milan Masar; Hassan Ali; Muhammad Yasir; Barbora Hanulikova; Orhan Sisman; Michal Zitnan; Michal Machovsky; Jose J. Velazquez; Dusan Galusek; Ivo Kuritka (Chemosphere, 2024)

Servant leadership and citizenship behavior in the Pakistani tourism and hospitality industry: The role of harmonious environmental passion and a green work climate - Yasir Iftikhar; Muhammad Shahid Tufail; Marcos Ferasso; Rizwan Qaiser Danish (Journal of Environmental Management, 2024)

Architecting high-performance photocatalysts: A review of modified 2D/2D graphene/g-C3N4 heterostructures - Muhammad Yasir Akram; Tuba Ashraf; Lei Tong; Xiulian Yin; Hongjun Dong; Huiling Lu (Journal of Environmental Chemical Engineering, 2024)

Photocatalytically active layered double hydroxide-PVDF composite membranes for effective remediation of dyes contaminated water - Mukarram Zubair; Muhammad Yasir; Michal Machovsky; Nadeem Baig; Mohammad Saood Manzar; Jehad Abdulfatah Sadeq Odeh; Mohamed K. Hassan; Alaa Hawari; Jehad Odeh; Emre Cevik; Maryam Al-Ejji (Chemosphere, 2024)

Effect of supplementing epinephrine in maturation media on in-vitro developmental competence of cattle and buffalo oocytes - Abdul Khaliq; Muhammad Ameer Hamza; Talha Ashraf; Ali Husnain; Muhammad Yaseen; Abdul Rehman; Muhammad Binyameen; Muhammad Yasir Zahoor; Amjad Riaz (Theriogenology, 2024)

Mitigating cadmium exposure risk in rice with foliar nano-selenium: Investigations through Caco-2 human cell line in-vivo bioavailability assay - Bilal Hussain; Xianyuan Yin; Qiang Lin; Yasir Hamid; Muhammad Usman; Muhammad Laeeq-ur-Rehman Hashmi; Min Lu; Muhammad Imran Taqi; Zhenli He; Xiao e Yang (Environmental Pollution, 2024)

Effect of naringenin on post-thaw quality, fertility-associated gene expression and fertilization potential of buffalo (Bubalus bubalis) bull sperm - Ghulam Shabbir Khan; Muhammad Zahid Tahir; Muhammad Yasir Zahoor; Hifz-ul-Rahman; Amjad Riaz (Cryobiology, 2024)

Functionality of wheat straw-derived biochar enhanced its efficiency for actively capping Cd and Pb in contaminated water and soil matrices: Insights through batch adsorption and flow-through experiments - Yasir Hamid; Yonglong Chen; Qiang Lin; Muhammad Haris; Muhammad Usman; Muhammad Saqib Rashid; Ioannis Anastopoulos; Bilal Hussain; Hayssam M. Ali; Fakhir Hannan; Xianyuan Yin; Xiaoe Yang (Chemosphere, 2024)

Phytoremediation of Arsenic (As) in rice plants, mediated by strain IU31 through antioxidant responses and phytohormones synthesis - Ihsan Ullah; Yasir Anwar; Muhammad Faisal Siddiqui; Nadiah Alsulami; Raza Ullah (Environmental Pollution, 2024)

Geospatial identification of possible rainwater harvesting locations within a high-altitude Gilgit River basin, Pakistan - Madiha Asif; Muhammad Yaseen; Syed Umair Shahid; Yasir Latif; Salma Anwar; Sohail Abbas (Theoretical and Applied Climatology, 2024)
The management of water resources is no longer an option but a necessity especially in countries with a high rate of population growth like Pakistan. Pakistan has a high-water scarcity, an extremely varying topography, and is also one of the countries encountering the problem of climate change. Therefore, prudent utilization of available water resources is a matter in the plains of Pakistan as in its high-altitude regions. Instead of wasting water which is a valuable resource, rainwater harvesting is a way of saving rainwater as an alternative source of fresh water for better use. The aim of this study was to search for potential rainwater-harvesting areas in a high-altitude Gilgit River basin. This research employed the SCS-CN technique in estimating surface runoff in the GIS environment. The geospatial study used four input parameters: slope of the land, land covers, surface runoff and drainage density. The research concluded that some lands, especially those that are deserted in dry area and agricultural lands, can serve as the sites of rainwater harvesting, with only 4% of area that was highly suitable for the purpose. Nevertheless, 37% of the investigated area was shown as totally unviable for rainwater collection installations because of steep slopes and substantial volume of snow. Simultaneously, the rainwater storage design solutions suggested were check dam, percolation tank, and agricultural ponds with the area of 3.5%, 1%, and 0.75% of the given land area, respectively, for rainwater harvesting. The locations of potential catchment and planned rainwater harvesting structures would assist the local authorities and the policy makers to provide plans and design on the construction of water storages and also the optimization of water use.

Water contamination, childhood diarrhoea, and household willingness to pay for safe drinking water in Pakistani urban slums - Yasir Mehmood; Muhammad Arshad (Sustainable Water Resources Management, 2024)

Cold plasma: A success road to mycotoxins mitigation and food value edition - Bilal Murtaza; Lili Wang; Xiaoyu Li; Muhammad Kashif Saleemi; Muhammad Yasir Nawaz; Mengyao Li; Yongping Xu (Food Chemistry, 2024)

Recent advancements in polyurethane-based membranes for gas separation - Noureen Arshad; Syeda Rubab Batool; Sadia Razzaq; Mubeen Arshad; Abher Rasheed; Munir Ashraf; Yasir Nawab; Muhammad Anwaar Nazeer (Environmental Research, 2024)

Root exudate compounds change the bacterial community in bulk soil - Muhammad Yasir Afzal; Bikram K. Das; Vishnu Thayil Valappil; Joy Scaria; Volker S. Brözel (Rhizosphere, 2024)

Photocatalytic and biological efficacy of Carissa macrocarpa fruit extract-mediated one-pot synthesized ternary metal oxide dual S-scheme heterojunction - Abu Bakar Siddique; Muhammad Ashraf Shaheen; Azhar Abbas; Yasir Zaman; Akbar Ali; Muhammad Naeem-ul-Hassan; Javed Iqbal (Journal of Environmental Chemical Engineering, 2024)

Understanding of the potential role of carbon dots in promoting interspecies electron transfer process in anaerobic co-digestion under magnetic field: Focusing on methane and hydrogen production - Yangyang Gao; Sining Yun; Kaijun Wang; Lijianan Liu; Yasir Abbas; Muhammad Saqlain Jamil; Teng Ke; Jiayu Liu; Xiaoxue Zhang (Chemical Engineering Journal, 2024)

Yeast-based solutions in controlling plant pathogens - Amjad Ali; Fatih Ölmez; Muhammad Ahmad Zeshan; Mustansar Mubeen; Yasir Iftikhar; Ashara Sajid; Muhammad Abid; Ajay Kumar; Praveen Kumar Divvela; Manoj Kumar Solanki (Biocatalysis and Agricultural Biotechnology, 2024)

Novel polynomial Abet data augmentation algorithm with GRU paradigm for nuclear power prediction - Saifullah Khan; Saeed Ehsan Awan; Yasir Muhammad; Ihtesham Jadoon; Muhammad Asif Zahoor Raja (Annals of Nuclear Energy, 2024)

Electricity shortfalls and financial leverage of listed firms in Pakistan - Muhammad Akhtar; Muhammad Haris; Hafiz Muhammad Naveed; Yasir Rasool; Mamdouh Abdulaziz Saleh Al-Faryan (Utilities Policy, 2024)

Effects of pulsed Nd:YAG laser kernel irradiation on maize (Zea mays L.): Insights into germination, gas exchange, photosynthetic pigments, and morphological modifications - Rashida Perveen; Yasir Jamil; Arwa Abdulkreem AL-Huqail; Ibtisam Mohammed Alsudays; Suliman Mohammed Suliman Alghanem; Qasim Ali; Farah Saeed; Muhammad Azeem; Muhammad Rizwan; Sami Asir Al-Robai (Journal of Photochemistry and Photobiology B: Biology, 2024)

Potential of Capparis decidua plant and eggshell composite adsorbent for effective removal of anionic dyes from aqueous medium - Ghulam Mujtaba; Abdul Hai; Mansoor Ul Hassan Shah; Asad Ullah; Yasir Anwar; Furqan Shah; Muhammad Daud; Afzal Hussain; Faheem Ahmed; Fawzi Banat (Environmental Research, 2024)

Recent advances in nanocellulose-based two-dimensional nanostructured membranes for sustainable water purification: A review - Mukarram Zubair; Muhammad Yasir; Deepalekshmi Ponnamma; Hassam Mazhar; Vladimir Sedlarik; Alaa H. Hawari; Mamdouh Ahmed Al-Harthi; Maryam Al-Ejji (Carbohydrate Polymers, 2024)

Modeling spatial distribution of earthquake epicenters using inhomogeneous Log-Gaussian Cox point process - Salma Anwar; Muhammad Yaseen; Muhammad Yaseen; Yasir Latif (Modeling Earth Systems and Environment, 2024)

Utilizing residual networks for remote sensing estimation of total nitrogen concentration in Shandong offshore areas - Hongxia Zheng; Yulin Wu; Haifeng Han; Juan Wang; Shanwei Liu; Mingming Xu; Jianyong Cui; Muhammad Yasir (Frontiers in Marine Science, 2024)
Nitrogen is one of the critical factors in water pollution and eutrophication, so applying the deep learning method in remote sensing inversion of nitrogen can provide basic information for environmental management. This paper proposes a two-step feature extraction method to solve the problem that the number of bands in water quality inversion is insufficient and the deep learning method cannot be fully exploited. Firstly, manual feature extraction is completed through the fusion between bands to obtain a set of high-latitude shallow factors, which make the features rich and diverse. Then, a one-dimensional convolutional residual network (ResNet-1D) is constructed, and the deep features are automatically extracted through convolution operations of the model, where the residual learning is used to reduce the training difficulty. The full connection is established through depth features. The comparison of models shows that the Mean Relative Error (MRE) is decreased by at least 10% in both test and validation datasets. Finally, the spatiotemporal distribution of total nitrogen concentration (TNC) in the coastal waters of Shandong is explored. In general, the spatial distribution is that the concentration near the coast is higher than the far. The temporal variation is that the monthly mean of the TNC is low in March, moderate in May and August, and high in October; the annual average value of TNC is 0.3mg/L, which has decreased slightly year by year since 2014.

Eocene nannofossils and paleoenvironmental reconstruction of the Kuldana Formation in Yadgar area, Muzaffarabad, northern Pakistan - Amir Shahzad; Jahanzeb Khan; Muhammad Hanif; Claudia Baumgartner-Mora; Yasir Sarfraz; Khawaja Shoaib Ahmed; Muhammad Tayyib Riaz; Peter O. Baumgartner; Munir ul Hassan Munir; Adnan Wazir (Palaeoworld, 2024)

Concentration and distribution patterns of rare earth elements (REEs) in stream sediments of Pakistan - Zhihua Wang; Jun Hong; Xin Lin; Huishan Zhang; Yasir Shaheen Khalil; Naghma Haider; Mehboob Ur Rashid; Muhammad Jawad Zeb; Asad Ali Narejo (Journal of Geochemical Exploration, 2024)

Seed nano-priming with multiple nanoparticles enhanced the growth parameters of lettuce and mitigated cadmium (Cd) bio-toxicity: An advanced technique for remediation of Cd contaminated environments - Nabila Bano; Sangar Khan; Yasir Hamid; Faiza Bano; Abdul Ghaffar Khan; Muhammad Asmat Ullah; Tingqiang Li; Habib Ullah; Nanthi Bolan; Jörg Rinklebe; Sabry M. Shaheen (Environmental Pollution, 2024)

First insights into per-and polyfluoroalkyl substance contamination in edible fish species of the Indus water system of Pakistan - Rahat Riaz; Muhammad Yasir Abdur Rehman; Muhammad Junaid; Taimoor Iqbal; Jawad Aslam Khan; Yanran Dong; Linxia Yue; Yupeng Chen; Nan Xu; Riffat Naseem Malik (Chemosphere, 2024)

Assessing the effectiveness of 3, 4-dimethylpyrazole phosphate (DMPP) inhibitor in mitigating N2O emissions from contrasting Cd-contaminated soils - Muhammad Laeeq Ur Rehman Hashmi; Yasir Hamid; Muhammad Usman; Jipeng Luo; Sangar Khan; Tang Sheng; Nabila Bano; TalhaTufail Bhatti; Tingqiang Li (Science of The Total Environment, 2024)

Comparison between U-shaped structural deep learning models to detect landslide traces - Kinh Bac Dang; Cong Quan Nguyen; Quoc Cuong Tran; Hieu Nguyen; Trung Thanh Nguyen; Duc Anh Nguyen; Trung Hieu Tran; Phuong Thao Bui; Tuan Linh Giang; Duc Anh Nguyen; Tu Anh Lenh; Van Liem Ngo; et al. (Science of The Total Environment, 2024)

Association of magnetic-flyash in anaerobic co-digestion for biomethane optimization: Promoting biofilm formation - Yasir Abbas; Sining Yun; Kaijun Wang; Xiaomin Zhang; Muhammad Saqlain Jamil; Fayyaz Ali Shah; Xiaoxue Zhang; Yangyang Gao; Han Luo (Journal of Cleaner Production, 2024)

Does green finance reduce environmental degradation? The role of green innovation, environmental tax, and geopolitical risk in China - Muhammad Yasir Mehboob; Benjiang Ma; Muhammad Basit Mehboob; Yunsheng Zhang (Journal of Cleaner Production, 2024)

Recalling the reported toxicity assessment of deoxynivalenol, mitigating strategies and its toxicity mechanisms: Comprehensive review - Bilal Murtaza; Lili Wang; Xiaoyu Li; Muhammad Yasir Nawaz; Muhammad Kashif Saleemi; Aisha Khatoon; Xu Yongping (Chemico-Biological Interactions, 2024)

Therapeutic Physical Properties, Photocatalytic, and Anti-bacterial Activities of Hydrothermally Fabricated Cu-doped ZnO NPs - Muhammad Zahid Ishaque; Yasir Zaman; Yasir Yousaf; Muhammad Shahzad; Abu Bakar Siddique; Hira Zaman; Sarmad Ali; Nisar Ali (Water, Air, & Soil Pollution, 2024)

Unlocking green innovation and environmental performance: the mediated moderation of green absorptive capacity and green innovation climate - Sadaf Akhtar; Cai Li; Jan Muhammad Sohu; Yasir Rasool; Muhammad Iatzaz Ul Hassan; Muhammad Bilal (Environmental Science and Pollution Research, 2023)

Unraveling the combined deleterious effects of ochratoxin A and atrazine upon broiler’s health: Toxicopathological, serum biochemical and immunological perspectives - Aisha Khatoon; Muhammad Yasir Nawaz; Ghazala Mehboob; Muhammad Kashif Saleemi; Shafia Tehseen Gul; Rao Zahid Abbas; Muhammad Umar Ijaz; Bilal Murtaza; Sheraz Ahmed Bhatti; Zain ul Abidin; Aamir Riaz Khan (Toxicon, 2023)

Design and fabrication of TiO2/Nd polyurethane nanofibers based photoreactor: A continuous flow kinetics study for Estriol degradation and mechanism - Muhammad Yasir; Hassan Ali; Milan Masar; Fahanwi Asabuwa Ngwabebhoh; Mukarram Zubair; Tomas Sopik; Michal Machovsky; Ivo Kuritka; Vladimir Sedlarik (Journal of Water Process Engineering, 2023)

Current trends in environmental and energy photocatalysis and ISO standardization - Hassan Ali; Milan Masar; Muhammad Yasir; Michal Machovsky; Olinda C. Monteiro; Ivo Kuritka (Journal of Environmental Chemical Engineering, 2023)

Retention of methyl iodide on metal and TEDA impregnated activated carbon using indigenously developed setup - Talhat Yaqoob; Masroor Ahmad; Yasir Faiz; Farman Ali; Amjad Farooq; Faisal Faiz; Attaullah Shah; Muhammad Asim Irshad; Naseem Irfan; Nisar Ali; Sahid Mehmood (Environmental Research, 2023)

Recent advances in chitosan-based materials; The synthesis, modifications and biomedical applications - Yasir Iqbal; Iqbal Ahmed; Muhammad Faisal Irfan; Shahzad Ali Shahid Chatha; Muhammad Zubair; Aman Ullah (Carbohydrate Polymers, 2023)

Characterization, Source Apportionment and Health Risk Assessment of Trace Metals in Groundwater of Metropolitan Area in Lahore, Pakistan - Yasir Karim Khan; Muhammad Toqeer; Munir H. Shah (Exposure and Health, 2023)

Influence of Phosphate Solubilizing Bacteria on the Growth of mustard Grown Under Drought Stress Conditions - Farhat Suhail; Aftab Afzal; Laraib Naseer; Aneela Pervaiz; Muhammad Ikram; Summaira Shaheen; Yasir Islam; Naeem Khan (Agricultural Research, 2023)

g-C3N4/graphene oxide/SnFe2O4 ternary composite for the effective sunlight-driven photocatalytic degradation of methylene blue - Suman Tahir; Muhammad Zahid; Muhammad Asif Hanif; Muhammad Yasir Javed (Environmental Science and Pollution Research, 2023)

Sugarcane-bagasse-ash in enhanced mesophilic Co-digestion for biogas and nutrient recovery: A concept of developing rural circular bioeconomy - Shahid Mumtaz; Yasir Abbas; Iftikhar Ahmad; Ahmed Hassan; Muhammad Farhan Saeed; Sining Yun; Zainab M. Almarhoon; Mohamed Shelkh; Ahmed M. Hassan; P. Rosaiah; Maduru Suneetha; Awais Ahmad (Environmental Research, 2023)

Patterns of coral diseases linked to the impact of climate change: a case study of scleractinia corals in Southeast Sulawesi, Indonesia’s coral triangle - La Ode Muhammad Yasir Haya; Ratna Diyah Palupi; Subhan Subhan; Rahmadani Rahmadani (Modeling Earth Systems and Environment, 2023)

Ranking Ship Detection Methods Using SAR Images Based on Machine Learning and Artificial Intelligence - Muhammad Yasir; Abdoul Jelil Niang; Md Sakaouth Hossain; Qamar Ul Islam; Qian Yang; Yuhang Yin (Journal of Marine Science and Engineering, 2023)
We aimed to improve the performance of ship detection methods in synthetic aperture radar (SAR) images by utilizing machine learning (ML) and artificial intelligence (AI) techniques. The maritime industry faces challenges in collecting precise data due to constantly changing sea conditions and weather, which can affect various maritime operations, such as maritime security, rescue missions, and real-time monitoring of water boundaries. To overcome these challenges, we present a survey of AI- and ML-based techniques for ship detection in SAR images that provide a more effective and reliable way to detect and classify ships in a variety of weather conditions, both onshore and offshore. We identified key features frequently used in the existing literature and applied the graph theory matrix approach (GTMA) to rank the available methods. This study’s findings can help users select a quick and efficient ship detection and classification method, improving the accuracy and efficiency of maritime operations. Moreover, the results of this study will contribute to advancing AI- and ML-based techniques for ship detection in SAR images, providing a valuable resource for the maritime industry.

Pharmacological and toxicological evaluation of methyl 4-hydroxy-2H-1,2-benzothiazine-3-carboxylate 1,1-dioxoide against haloperidol induced Parkinson like symptoms in animal model: In-vitro and in-vivo studies - Liaqat Hussain; Ina Masood; Matloob Ahmad; Muhammad Yasir Ali; Uzma Saleem; Musaddique Hussain; Syed Haroon Khalid; Zunera Chauhdary (Toxicology and Applied Pharmacology, 2023)

Differential accumulation pattern of cadmium in plant parts of pea varieties in response to varying cadmium levels - Khurram Ziaf; Hafiz Muhammad Talha; Muhammad Awais Ghani; Iftikhar Ahmad; Raheel Anwar; Basharat Ali; Yasir Majeed; Amir Shakeel; Mudassar Iqbal; Abbu Zaid (South African Journal of Botany, 2023)

Novel thiol-grafted composite of chitosan and rice straw biochar (TH@CT-BC): A two-step fabrication for highly selective adsorption of cadmium from contaminated water - Yasir Hamid; Lei Liu; Muhammad Haris; Muhammad Usman; Qiang Lin; Yonglong Chen; Muhammad Saqib Rashid; Zaid Ulhassan; M. Iftikhar Hussain; Xiaoe Yang (Journal of Environmental Chemical Engineering, 2023)

The impact of financial innovation, green energy, and economic growth on transport-based CO2 emissions in India: insights from QARDL approach - Snovia Naseem; Umair Kashif; Yasir Rasool; Muhammad Akhtar (Environment, Development and Sustainability, 2023)

Morphological change assessment of a coastal island in SE Bangladesh reveal high accumulation rates - Md Sakaouth Hossain; Muhammad Yasir; Md. Shams Shahriar; Maftuha Jahan; Shanwei Liu; Abdoul Jelil Niang (Regional Studies in Marine Science, 2023)

Seed priming with nano-silica effectively ameliorates chromium toxicity in Brassica napus - Zaid Ulhassan; Su Yang; Di He; Ali Raza Khan; Abdul Salam; Wardah Azhar; Sajid Muhammad; Skhawat Ali; Yasir Hamid; Imran Khan; Mohamed Salah Sheteiwy; Weijun Zhou (Journal of Hazardous Materials, 2023)

RETRACTED: Sustainable, economical and rapid treatment of multiple lung diseases using therapeutic potential of curcumin nanoparticles - Qudsia Kanwal; Samiah Shahid; Abeel Ahmad; Arif Nazir; Muhammad Yasir; Aneela Anwar; Samar Z. Alshawwa; Munawar Iqbal (Environmental Research, 2023)

A new decomposition model of sea level variability for the sea level anomaly time series prediction - Qinting Sun; Jianhua Wan; Shanwei Liu; Jinghui Jiang; Yasir Muhammad (Journal of Oceanology and Limnology, 2023)

Effect of foliar application of nanoparticles on growth, physiology, and antioxidant enzyme activities of lettuce (Lactuca sativa L.) plants under cadmium toxicity - Nabila Bano; Sangar Khan; Yasir Hamid; Muhammad Asmat Ullah; Abdul Ghaffar Khan; Faiza Bano; Jipeng Luo; Tingqiang Li (Environmental Science and Pollution Research, 2023)

Physical properties of multifunctional TM-doped ZnO nanorods and their photocatalytic and anti-bacterial activities - Yasir Zaman; Muhammad Zahid Ishaque; Yasir Yousaf; Muhammad Shahzad; Abu Bakar Siddique; Muhammad Imran Arshad; Muhammad Sajid; Nisar Ali; Ghulam Nabi (Environmental Science and Pollution Research, 2023)

Enhancement of combustion effect leading to improved performance and exhaust emissions of an SI engine with ferrous oxide and graphite nanoparticles - Yasir Hussain Siddiqui; Muhammad Shakaib; Adnan Rasheed; Hafiz Muhammad Ali; Syed Mohammad Rizwan Azeem; Athar Husain Siddique; Muhammad Shafiq (Environmental Science and Pollution Research, 2023)

Evaluating the effects of soil physicochemical properties under different land use types in the arid zones of Pakistan - Muhammad Yaseen; Sohail Abbas; Yasir Latif (Environment, Development and Sustainability, 2023)

Green financing strategy for low-carbon economy: The role of high-technology imports and institutional strengths in China - Taimoor Hassan; Yasir Khan; Adnan Safi; He Chaolin; Salman Wahab; Abdul Daud; Muhammad Tufail (Journal of Cleaner Production, 2023)

Microbial biochemical pathways of arsenic biotransformation and their application for bioremediation - Hareem Mohsin; Maria Shafique; Muhammad Zaid; Yasir Rehman (Folia Microbiologica, 2023)

3D and 4D Bioprinting Technologies: A Game Changer for the Biomedical Sector? - Reza Noroozi; Zia Ullah Arif; Hadi Taghvaei; Muhammad Yasir Khalid; Hossein Sahbafar; Amin Hadi; Ali Sadeghianmaryan; Xiongbiao Chen (Annals of Biomedical Engineering, 2023)

An improved semantic segmentation model based on SVM for marine oil spill detection using SAR image - Dawei Wang; Shanwei Liu; Chao Zhang; Mingming Xu; Junfang Yang; Muhammad Yasir; Jianhua Wan (Marine Pollution Bulletin, 2023)

Assessing the role of green supply chain management in enhancing Pakistan manufacturers’ performances - Muhammad Ibrahim Tariq; Kashif Abbass; Kaouther Chebbi; Yasir Hussain (Environmental Science and Pollution Research, 2023)

Coastal landscape classification using convolutional neural network and remote sensing data in Vietnam - Tuan Linh Giang; Quang Thanh Bui; Thi Dieu Linh Nguyen; Van Bao Dang; Quang Hai Truong; Trong Trinh Phan; Hieu Nguyen; Van Liem Ngo; Van Truong Tran; Muhammad Yasir; Kinh Bac Dang (Journal of Environmental Management, 2023)

Removal of COD from real oily wastewater by electrocoagulation using a new configuration of electrodes - Muhammad Aiyd Jasim; Forat Yasir AlJaberi (Environmental Monitoring and Assessment, 2023)

In-field deployable and facile nanosensor for the detection of pesticides residues - Naveed Akhtar Shad; Anam Munawar; Yasir Javed; Allah Rakha; Ahsan Riaz; Salah Ud Din; Iqra Zareef; Muhammad Munir Sajid; Muahmmad Farhan Khan; Sareen Akhtar; Midhat Salman (Analytica Chimica Acta, 2023)

Health risk assessment associated with heavy metals through fractioned dust from coal and chromite mines in Pakistan - Zakia Sultana; Muhammad Yasir Abdur Rehman; Hudda Khaleeq Khan; Riffat Naseem Malik (Environmental Geochemistry and Health, 2023)

Mobility, bioaccessibility, pollution assessment and risk characterization of potentially toxic metals in the urban soil of Lahore, Pakistan - Yasir Karim Khan; Muhammad Toqeer; Munir H. Shah (Environmental Geochemistry and Health, 2023)

Instance segmentation ship detection based on improved Yolov7 using complex background SAR images - Muhammad Yasir; Lili Zhan; Shanwei Liu; Jianhua Wan; Md Sakaouth Hossain; Arife Tugsan Isiacik Colak; Mengge Liu; Qamar Ul Islam; Syed Raza Mehdi; Qian Yang (Frontiers in Marine Science, 2023)
It is significant for port ship scheduling and traffic management to be able to obtain more precise location and shape information from ship instance segmentation in SAR pictures. Instance segmentation is more challenging than object identification and semantic segmentation in high-resolution RS images. Predicting class labels and pixel-wise instance masks is the goal of this technique, which is used to locate instances in images. Despite this, there are now just a few methods available for instance segmentation in high-resolution RS data, where a remote-sensing image’s complex background makes the task more difficult. This research proposes a unique method for YOLOv7 to improve HR-RS image segmentation one-stage detection. First, we redesigned the structure of the one-stage fast detection network to adapt to the task of ship target segmentation and effectively improve the efficiency of instance segmentation. Secondly, we improve the backbone network structure by adding two feature optimization modules, so that the network can learn more features and have stronger robustness. In addition, we further modify the network feature fusion structure, improve the module acceptance domain to increase the prediction ability of multi-scale targets, and effectively reduce the amount of model calculation. Finally, we carried out extensive validation experiments on the sample segmentation datasets HRSID and SSDD. The experimental comparisons and analyses on the HRSID and SSDD datasets show that our model enhances the predicted instance mask accuracy, enhancing the instance segmentation efficiency of HR-RS images, and encouraging further enhancements in the projected instance mask accuracy. The suggested model is a more precise and efficient segmentation in HR-RS imaging as compared to existing approaches.

Photocatalytic and Antibacterial Potential of Silver Nanocubes and Nanorods Synthesized via Polyol Reduction Method - Muhammad Zahid Ishaque; Yasir Zaman; Muhammad Shahzad; Abu Bakar Siddique; Sana Shahid; Muhammad Akram; Humaira Kanwal; Muhammad Tahir Akhtar; Safdar Hussain (Water, Air, & Soil Pollution, 2023)

Description of novel variants in consanguineous Pakistani families affected with intellectual disability - Iqra Ghulam Rasool; Muhammad Yasir Zahoor; Irfan Ahmed; Muhammad Iqbal; Shehla Shafqat; Aftab Ahmad Anjum; Wasim Shehzad (Genes & Genomics, 2023)

Spatial Pattern of Cotton Yield Variability and Its Response to Climate Change in Cotton Belt of Pakistan - Naveed Muhammad; Hongshi He; Shengwei Zong; Haibo Du; Zulqarnain Satti; Xinyuan Tan; Muhammad Yasir Qazi (Chinese Geographical Science, 2023)

Lightweight algorithm for multi-scale ship detection based on high-resolution SAR images - Weimin Kong; Shanwei Liu; Mingming Xu; Muhammad Yasir; Dawei Wang; Wantao Liu (International Journal of Remote Sensing, 2023)

Prediction and interpretation of antibiotic-resistance genes occurrence at recreational beaches using machine learning models - Sara Iftikhar; Asad Mustafa Karim; Aoun Murtaza Karim; Mujahid Aizaz Karim; Muhammad Aslam; Fazila Rubab; Sumera Kausar Malik; Jeong Eun Kwon; Imran Hussain; Esam I. Azhar; Se Chan Kang; Muhammad Yasir (Journal of Environmental Management, 2023)

Bacillus Species as Direct-Fed Microbial Antibiotic Alternatives for Monogastric Production - Shifa A. Bahaddad; Meshal H. K. Almalki; Othman A. Alghamdi; Sayed S. Sohrab; Muhammad Yasir; Esam I. Azhar; Hichem Chouayekh (Probiotics and Antimicrobial Proteins, 2023)

Multi-scale ship target detection using SAR images based on improved Yolov5 - Muhammad Yasir; Liu Shanwei; Xu Mingming; Sheng Hui; Md Sakaouth Hossain; Arife Tugsan Isiacik Colak; Dawei Wang; Wan Jianhua; Kinh Bac Dang (Frontiers in Marine Science, 2023)
Synthetic aperture radar (SAR) imaging is used to identify ships, which is a vital task in the maritime industry for managing maritime fisheries, marine transit, and rescue operations. However, some problems, like complex background interferences, various size ship feature variations, and indistinct tiny ship characteristics, continue to be challenges that tend to defy accuracy improvements in SAR ship detection. This research study for multiscale SAR ships detection has developed an upgraded YOLOv5s technique to address these issues. Using the C3 and FPN + PAN structures and attention mechanism, the generic YOLOv5 model has been enhanced in the backbone and neck section to achieve high identification rates. The SAR ship detection datasets and AirSARship datasets, along with two SAR large scene images acquired from the Chinese GF-3 satellite, are utilized to determine the experimental results. This model’s applicability is assessed using a variety of validation metrics, including accuracy, different training and test sets, and TF values, as well as comparisons with other cutting-edge classification models (ARPN, DAPN, Quad-FPN, HR-SDNet, Grid R-CNN, Cascade R-CNN, Multi-Stage YOLOv4-LITE, EfficientDet, Free-Anchor, Lite-Yolov5). The performance values demonstrate that the suggested model performed superior to the benchmark model used in this study, with higher identification rates. Additionally, these excellent identification rates demonstrate the recommended model’s applicability for maritime surveillance.

Coupling of deep learning and remote sensing: a comprehensive systematic literature review - Muhammad Yasir; Wan Jianhua; Liu Shanwei; Hui Sheng; Xu Mingming; Md Hossain (International Journal of Remote Sensing, 2023)

Spatial distribution, compositional profile, sources, ecological and human health risks of legacy and emerging per- and polyfluoroalkyl substances (PFASs) in freshwater reservoirs of Punjab, Pakistan - Rahat Riaz; Muhammad Junaid; Muhammad Yasir Abdur Rehman; Taimoor Iqbal; Jawad Aslam Khan; Yanran Dong; Linxia Yue; Yupeng Chen; Nan Xu; Riffat Naseem Malik (Science of The Total Environment, 2023)

Role of biochar-based free radicals in immobilization and speciation of metals in the contaminated soil-plant environment - Muhammad Saqib Rashid; Guijian Liu; Balal Yousaf; Yasir Hamid; Abdul Rehman; Muhammad Arif; Rafay Ahmed; Yu Song; Aniqa Ashraf (Journal of Environmental Management, 2023)

REEs enriched heavy minerals from the river and beach sands of Bangladesh - Md Sakaouth Hossain; Azizur Rahman; Md. Shams Shahriar; Zahidul Bari; Muhammad Yasir (Arabian Journal of Geosciences, 2023)

Facile synthesis and comparative study of the enhanced photocatalytic degradation of two selected dyes by TiO2-g-C3N4 composite - Asma A. Alothman; Asif Ayub; Safa K. Hachim; Borhan Mustafa Mohammed; Farhat Hussain; Muhammad Altaf; Zainab Jawad Kadhim; Holya A. Lafta; Yasir S. Alnassar; Marwah A. Shams; Nada A. Almuhous; Mohamed Ouladsmane; et al. (Environmental Science and Pollution Research, 2022)

Foliar Application of Silicon Improved Physiological Indicators, Yield Attributes, and Yield of Pearl Millet (Pennisetum glaucum L.) Under Terminal Drought Stress - Allah Wasaya; Jamshaid Hassan; Tauqeer Ahmad Yasir; Muhammad Ateeq; Muhammad Ali Raza (Journal of Soil Science and Plant Nutrition, 2022)

Correction to: Interactive Effect of Boron Application Methods and Boron-Tolerant Bacteria (Bacillus sp. MN54) Improves Nodulation, Grain Yield, Profitability and Biofortification of kabuli Chickpea Grown Under Irrigated and Rainfed Conditions - Noman Mehboob; Tauqeer Ahmad Yasir; Sami Ul-Allah; Ahmad Nawaz; Muhammad Naveed; Mubshar Hussain (Journal of Soil Science and Plant Nutrition, 2022)

Coastline extraction based on multi-scale segmentation and multi-level inheritance classification - Sheng Hui; Guo Mengliang; Gan Yuliang; Xu Mingming; Liu Shanwei; Muhammad Yasir; Cui Jianyong; Wan Jianhua (Frontiers in Marine Science, 2022)
Detailed management of the coastline is critical to the development of coastal states. However, the current classification of the coastline is relatively weak. This study proposed an automatic method to detect coastlines with category attributes based on multi-scale segmentation and multi-level inheritance classification. Fully integrating the advantages of multi-scale segmentation and multi-level classification, it solved the problems that traditional methods could not solve, such as extracting coastlines with categorical attributes, cultivation ponds that are easily affected by tidal flats, and complex coastal terrain. The Chinese GF-2 satellite images are used to extract various types of coastlines in Jiaozhou Bay and its surrounding areas such as the harbor-wharf coastline, silt coastline, pond coastline, rocky coastline, and sandy coastline. Compared with the human interpretation, it is found that the coastline extracted by our proposed method is different by 10.104 km in the harbor-wharf coastline, 0.099 km in the silt coastline, 2.677 km in the pond coastline, 8.831 km in the rocky coastline, and 0.218 km in the sandy coastline. Furthermore, compared to the object-based region growing integrating edge detection (OBRGIE) method, it is increased by 13.52%, 2.16%, 14.48%, 52.57%, and 22.97%, respectively. The results show that our proposed method is algorithmically more reasonable, accurate, and powerful. It can provide data support for refined coastline management.

Assessing long-term coral reef degradation in Indonesia’s Tiworo strait marine conservation area using remote sensing and rapid appraisal for fisheries approaches - La Ode Muhammad Yasir Haya; Baru Sadarun; Muslim Tadjudah; Analuddin Kangkuso; La Ode Alirman Afu; Asrin Ginong Pratikino; Amadhan Takwir; Masahiko Fujii (Modeling Earth Systems and Environment, 2022)

Exploring the mediating role of environmental strategy, green innovations, and transformational leadership: the impact of corporate social responsibility on environmental performance - Yasir Hussain; Kashif Abbass; Muhammad Usman; Muhammad Rehan; Muhammad Asif (Environmental Science and Pollution Research, 2022)

Tanneries impact on groundwater quality: a case study of Kasur city in Pakistan - Hafiz Qasim Ali; Muhammad Umair Yasir; Amir Farooq; Mahrukh Khan; Muhammad Salman; Muhammad Waqar (Environmental Monitoring and Assessment, 2022)

Arsenic and fluoride co-exposure through drinking water and their impacts on intelligence and oxidative stress among rural school-aged children of Lahore and Kasur districts, Pakistan - Muhammad Saeed; Muhammad Yasir Abdur Rehman; Abida Farooqi; Riffat Naseem Malik (Environmental Geochemistry and Health, 2022)

Synthesis, characterization and biological evaluation of Bis-benzimidazolium salts and their silver(I)-N-heterocyclic carbene complexes - Rana Yasir Nadeem; Munazzah Yaqoob; WanSinn Yam; Rosenani A. Haque; Muhammad Adnan Iqbal (Medicinal Chemistry Research, 2022)

Extracellular vesicles and exosome: insight from physiological regulatory perspectives - Muhammad Yasir Waqas; Muhammad Arshad Javid; Muhammad Mudasser Nazir; Nasir Niaz; Muhammad Farrukh Nisar; Zahid Manzoor; Sheraz Ahmed Bhatti; Sajid Hameed; Muhammad Haseeb Khaliq (Journal of Physiology and Biochemistry, 2022)

Temperature-Dependent Speciation Analysis of Chromium Immobilized in Calcium Hydroxyapatite Matrix - Sajid Iqbal; Yasir Faiz; Messaoud Harfouche; Muhammad Saifullah; Jong-Il Yun (International Journal of Environmental Research, 2022)

The nexus between CO2 emissions, human capital, technology transfer, and renewable energy: evidence from Belt and Road countries - Yasir Khan; Taimoor Hassan; Muhammad Tufail; Mohamed Marie; Muhammad Imran; Zhang Xiuqin (Environmental Science and Pollution Research, 2022)

Integrated application of plant bioregulator and micronutrients improves crop physiology, productivity and grain biofortification of delayed sown wheat - Naeem Ahmad; Ahmad Latif Virk; Sadam Hussain; Muhammad Bilal Hafeez; Fasih Ullah Haider; Muhammad Ishaq Asif Rehmani; Tauqeer Ahmad Yasir; Ariba Asif (Environmental Science and Pollution Research, 2022)

ATP-binding cassette transporters expression profiling revealed its role in the development and regulating stress response in Solanum tuberosum - Madiha Zaynab; Zongkang Wang; Athar Hussain; Khalida Bahadar; Mateen Sajid; Yasir Sharif; Muhammad Azam; Kalsoom Sughra; Muhammad Ammar Raza; Khalid Ali Khan; Shuangfei Li (Molecular Biology Reports, 2022)

Methotrexate-loaded biodegradable nanoparticles exert anti-arthritic effect by downregulating pro-inflammatory cytokines in Freund’s complete adjuvant-induced arthritic rats - Muhammad Usman Saleem; Faqir Muhammad; Ali Sharif; Muhammad Imran Arshad; Kanwal Akhtar; Yasir Javed; Bushra Akhtar (Inflammopharmacology, 2022)

Metal biomonitoring using fractioned dust to investigate urinary and oxidative stress biomarkers among occupationally exposed chromite mine workers - Changaiz Khan; Muhammad Yasir Abdur Rehman; Riffat Naseem Malik (Environmental Science and Pollution Research, 2022)

Development of magnesium oxide@carbon fiber paper composite film for the removal of methyl orange from aqueous phase - Saeed Ahmed; Muhammad Yasir Akram; Ashutosh Kumar; Amit Dhir; Zahid Ali; Sushil Kumar Kansal; Jatinder Kumar Ratan (Nanotechnology for Environmental Engineering, 2022)

Illuminating Empirical Evidence of Climate Change: Impacts on Rice Production in the Punjab Regions, Pakistan - Sohail Abbas; Shazia Kousar; Safdar Ali Shirazi; Muhammad Yaseen; Yasir Latif (Agricultural Research, 2022)

Recent trends in the use of fly ash for the adsorption of pollutants in contaminated wastewater and soils: Effects on soil quality and plant growth - Muhammad Usman; Ioannis Anastopoulos; Yasir Hamid; Abdul Wakeel (Environmental Science and Pollution Research, 2022)

Comparative seismic performance assessment of RC and RC/ECC hybrid frame structures: a shake table study - Fasih Ahmed Khan; Muhammad Rashid; Sajjad Wali Khan; Muhammad Rizwan; Yasir Irfan Badrashi; Muhammad Fahim; Muhammad Ashraf Tanoli; Wasim Khaliq; Akhtar Gul (Innovative Infrastructure Solutions, 2022)

Review of hospital plastic waste management strategies for Pakistan - Yasir Qayyum Gill; Mudasar Khurshid; Umer Abid; Muhammad Wajid Ijaz (Environmental Science and Pollution Research, 2022)

Caring for the environment: measuring the dynamic impact of remittances and FDI on CO2 emissions in China - Muhammad Afaq Haider Jafri; Syed Abbas; Syed Muhammad Yasir Abbas; Sana Ullah (Environmental Science and Pollution Research, 2022)

Arabiibacter massiliensis gen. nov. sp. nov., New Anaerobic Bacterium Isolated from the Human Gut - Cheikh Ibrahima Lo; Sory Ibrahima Traore; Awa Diop; Melhem Bilen; Esam Ibraheem Azhar; Fehmida Bibi; Asif Jiman-Fatani; Muhammad Yasir; Jean-Christophe Lagier; Didier Raoult; Florence Fenollar; Pierre-Edouard Fournier (Current Microbiology, 2022)

Isolation and molecular characterization of Adenovirus in suspected acute flaccid paralysis patients: A preliminary report from Pakistan - Zainab Khattak; Aamer Ali Shah; Syed Sohail Zahoor Zaidi; Nayab Mahmood; Muhammad Masroor Alam; Salmaan Sharif; Ribqa Akhtar; Yasir Arshid; Muhammad Suleman Rana (Archives of Virology, 2022)

Fabrication of visible light active Mn-doped Bi2WO6-GO/MoS2 heterostructure for enhanced photocatalytic degradation of methylene blue - Noor Tahir; Muhammad Zahid; Ijaz Ahmad Bhatti; Yasir Jamil (Environmental Science and Pollution Research, 2022)

Analysis of food resources, host availability and insecticidal impacts on the fecundity, longevity and parasitism efficiency of Diaertiella rapae (M’intosh) - Ahmad Nawaz; Habib Ali; Sajid Fiaz; Muhammad Sufyan; Miza Abdul Qayyum; Rashid Azad; Yasir Niaz; Muhamamd Adnan Bodlah; Khalid Ali Khan (International Journal of Tropical Insect Science, 2021)

Do neonicotinoids better than pyrethroids for Coccinella septempunctata L. (Coleoptera: Coccinellidae)? A comparative sub-lethal indirect age-stage, two-sex life tables laboratory bioassay - Muhammad Rizwan; Bilal Atta; Misbah Rizwan; Ijaz Ashraf; Muhammad Arshad; Muhammad Tahir; Mudassir Ali; Arshed Makhdoom Sabir; Muhammad Bilal; Muhammad Yasir Ali (International Journal of Tropical Insect Science, 2021)

Heavy metal-associated oxidative stress and glutathione s-transferase polymorphisms among E-waste workers in Pakistan - Muneeb Tahir; Muhammad Yasir Abdur Rehman; Riffat Naseem Malik (Environmental Geochemistry and Health, 2021)

Role of nanotechnology in animal production and veterinary medicine - Ahmad Ali; Muhammad Ijaz; Yasir Razzaq Khan; Hina Afzal Sajid; Kashif Hussain; Ameer Hamza Rabbani; Muhammad Shahid; Omer Naseer; Awais Ghaffar; Muhammad Anas Naeem; Muhammad Zeeshan Zafar; Amir Iftikhar Malik; et al. (Tropical Animal Health and Production, 2021)

Knowledge, attitude, and practices associated with brucellosis among livestock owners and its public health impact in Punjab, Pakistan - Sabir Hussain; Abrar Hussain; Ubaid-ur-Rehman Zia; Syed Musa Raza Naqvi; Muhammad Yasir Zahoor; Muhammad Bilal; Jeffery HO; Olivier A. E. Sparagano (Biologia, 2021)

Clostridium culturomicium sp. nov. and Clostridium jeddahitimonense sp. nov., novel members of the Clostridium genus isolated from the stool of an obese Saudi Arabian - Hoang Thong Kieu; Noémie Garrigou; Amael Fadlane; Ludivine Brechard; Nicholas Armstrong; Philippe Decloquement; Muhammad Yasir; Esam Ibraheem Azhar; Saad B. Al-Masaudi; Jean-Christophe Lagier; Maryam Tidjani Alou; Didier Raoult (Current Microbiology, 2021)

Regional disparities in Preventive measures of COVID-19 pandemic in China. A study from international students’ prior knowledge, perception and vulnerabilities - Ijaz Younis; Cheng Longsheng; Muhammad Imran Zulfiqar; Muhammad Imran; Syed Ahsan Ali Shah; Mudassar Hussain; Yasir Ahmed Solangi (Environmental Science and Pollution Research, 2021)

Bismuth vanadate/MXene (BiVO4/Ti3C2) heterojunction composite: enhanced interfacial control charge transfer for highly efficient visible light photocatalytic activity - Muhammad Munir Sajid; Sadaf Bashir Khan; Yasir Javed; Nasir Amin; Zhengjun Zhang; Naveed Akhtar Shad; Haifa Zhai (Environmental Science and Pollution Research, 2021)

Mitigating Drought Stress in Sunflower (Helianthus annuus L.) Through Exogenous Application of β-Aminobutyric Acid - Allah Wasaya; Tanveer Abbas; Tauqeer Ahmad Yasir; Naeem Sarwar; Ahsan Aziz; Muhammad Mansoor Javaid; Sheeraz Akram (Journal of Soil Science and Plant Nutrition, 2021)

Geotechnical investigation and landslide susceptibility assessment along the Neelum road: a case study from Lesser Himalayas, Pakistan - Khawaja Shoaib Ahmed; Muhammad Basharat; Muhammad Tayyib Riaz; Yasir Sarfraz; Amir Shahzad (Arabian Journal of Geosciences, 2021)

Whole exome sequencing revealed novel variants in consanguineous Pakistani families with intellectual disability - Iqra Ghulam Rasool; Muhammad Yasir Zahoor; Muhammad Iqbal; Aftab Ahmad Anjum; Fatima Ashraf; Hafiz Qamar Abbas; Hafiz Muhammad Azhar Baig; Tariq Mahmood; Wasim Shehzad (Genes & Genomics, 2021)

Alkaline lipase production by novel meso-tolerant psychrophilic Exiguobacterium sp. strain (AMBL-20) isolated from glacier of northeastern Pakistan - Muhammad Talha Yasin; Yasir Ali; Khurshid Ahmad; Abdul Ghani; Kinza Amanat; Muhammad Mudassir Basheir; Muhammad Faheem; Saddam Hussain; Bashir Ahmad; Adil Hussain; Syed Ali Imran Bokhari (Archives of Microbiology, 2021)

Foliage applied potassium improves stay green, photosynthesis and yield of maize (Zea mays L.) under rainfed condition - Allah Wasaya; Tauqeer Ahmad Yasir; Naeem Sarwar; Omer Farooq; Atique ur Rehman; Khuram Mubeen; Muqarrab Ali; Muhammad Affan; Ahsan Aziz (Plant Physiology Reports, 2021)

Synthesis, urease inhibition screening and molecular docking studies of piperonal based imine derivatives - Obaid-ur-Rahman Abid; Saima Daud; Asma Sardar; Wajid Rehman; Abdul Wadood; Ashfaq Ur Rehman; Toheed Akhter; Iram Bibi; Zaheer Ahmad; Muhammad Yasir (Medicinal Chemistry Research, 2021)

Optimizing Boron Seed Coating Level and Boron-Tolerant Bacteria for Improving Yield and Biofortification of Chickpea - Mubshar Hussain; Noman Mehboob; Muhammad Naveed; Kousar Shehzadi; Tauqeer Ahmad Yasir (Journal of Soil Science and Plant Nutrition, 2020)

Elevated exposure to polycyclic aromatic hydrocarbons (PAHs) may trigger cancers in Pakistan: an environmental, occupational, and genetic perspective - Muhammad Yasir Abdur Rehman; Malik Mumtaz Taqi; Imran Hussain; Jawad Nasir; Syed Hussain Haider Rizvi; Jabir Hussain Syed (Environmental Science and Pollution Research, 2020)

Assessing inflow variability at rim stations of the Indus Basin Irrigation System * - Yasir Abbas; Noor Muhammad Khan; Habib‐Ur‐Rehman Mughal; Khalid Mahmood (Irrigation and Drainage, 2020)
Having one of the largest interconnected irrigation systems in the world, the distribution of irrigation water in Pakistan is largely dependent on river supplies. Seasonal planning of water distribution in the country ignores day‐to‐day inflow variability which impacts water distribution operations. This study has been carried out to assess the inflow variability at four rim stations of the Indus Basin Irrigation System (IBIS) in Pakistan, namely: Kabul River at Noshera, Indus River at Tarbela, Jhelum River at Mangla, and Chenab River at Marala. Nine vital hydrological parameters, depicting various aspects of variability, were computed using 24 years of daily inflow time series. Analysis indicated that Mangla and Marala stations depicted more instances of high flow pulses, which highlighted their flashy nature compared to Noshera and Tarbela whose contributions were mainly from snowmelt. Mangla and Marala stations also depicted higher variations in terms of number and duration of low flow pulses, whereas least low flow variations were observed at Tarbela. Assessment of variability indicated that Tarbela exhibited minimum variations in inflows in the months of October to January, while Marala showed highest inflow variations among all stations in the same months. This study identified successfully the critical months of high flow variability, in addition to identification of the climate shift in the region—two aspects that need attention in future planning and operations.

Interaction of the surface bound antimicrobial peptides melimine and Mel4 with Staphylococcus aureus - Muhammad Yasir; Debarun Dutta; Naresh Kumar; Mark D. P. Willcox (Biofouling, 2020)

Single tube multiplex PCR assay for the identification of banned meat species - Memoona Iqbal; Muhammad Sulyman Saleem; Muhammad Imran; Waseem Ahmad Khan; Kamran Ashraf; M. Yasir Zahoor; Imran Rashid; Habib-Ur Rehman; Asif Nadeem; Saadat Ali; Sarwat Naz; Wasim Shehzad (Food Additives & Contaminants Part B-Surveillance, 2020)

Biofortification with Zinc and Iron Improves the Grain Quality and Yield of Wheat Crop - Yasir Ramzan; Muhammad Bilal Hafeez; Shahbaz Khan; Majid Nadeem; Saleem-ur-Rahman; Sumaira Batool; Javed Ahmad (International Journal of Plant Production, 2020)

Forecasting Nitrous Oxide emissions based on grey system models - Huaping Sun; Jingjing Jiang; Muhammad Mohsin; Jijian Zhang; Yasir Ahmed Solangi (Environmental Geochemistry and Health, 2020)

Valorization of solid waste biomass by inoculation for the enhanced yield of biogas - Yasir Abbas; Farrukh Jamil; Sikander Rafiq; Moinuddin Ghauri; M. Shahzad Khurram; Muhammad Aslam; Awais Bokhari; Abrar Faisal; Umer Rashid; Sining Yun; Muhammad Mubeen (Clean Technologies and Environmental Policy, 2020)

An effective modification of finite element method for heat and mass transfer of chemically reactive unsteady flow - Yasir Nawaz; Muhammad Shoaib Arif (Computational Geosciences, 2020)

Spatial analysis of temperature time series over the Upper Indus Basin (UIB) Pakistan - Yasir Latif; Ma Yaoming; Muhammad Yaseen; Sher Muhammad; Muhammad Atif Wazir (Theoretical and Applied Climatology, 2020)
Runoff generated from the Upper Indus Basin (UIB) mainly originates in the massifs of the Hindukush–Karakoram–Himalaya (HKH) region of Pakistan. Water supply in early spring depends upon the snow accumulation in the winter and the subsequent temperature. Seasonal temperature variations corroborate the contemporary dynamics of snow and glaciers. Recently, there has been increasing evidence of accelerated warming in high mountain areas, termed as elevation-dependent warming (EDW). We have identified trends, analyzed inconsistencies, and calculated changes in the maximum, minimum, mean and diurnal temperature range ( T max , T min , T mean , and DTR) at 20 weather stations during four-time series: 1961–2013 (first), 1971–2013 (second), 1981–2013 (third), and 1991–2013 (fourth). We employed the Mann–Kendall test to determine the existence of a trend and Sen’s method for the estimation of prevailing trends, whereas homogeneity analysis was applied before trend identification using three different tests. This study revealed that the largest and smallest magnitudes of trends appeared in the winter and summer, respectively, particularly during the fourth data series. T max revealed robust warming at ten stations, most remarkably at Gupis, Khunjrab, and Naltar at rates of 0.29, 0.36, and 0.43 °C/decade, respectively, during the fourth series. We observed that T min exhibits a mixed pattern of warming and cooling during the second and third series, but cooling becomes stronger during the fourth series, exhibiting significant trends at twelve stations. Khunjrab and Naltar showed steady warming during the fourth series (spring), at rates of 0.26 and 0.13 °C/decade in terms of T mean . The observed decreases in DTR appeared stronger in the fourth series during the summer. These findings tend to partially support the notion of EDW but validate the dominance of cooling spatially and temporally.

Dynamic linkages among CO2 emissions, human development, financial development, and globalization: empirical evidence based on PMG long-run panel estimation - Zhaohua Wang; Yasir Rasool; Muhammad Mansoor Asghar; Bo Wang (Environmental Science and Pollution Research, 2019)

Assessing the immobilization efficiency of organic and inorganic amendments for cadmium phytoavailability to wheat - Yasir Hamid; Lin Tang; Min Lu; Bilal Hussain; Afsheen Zehra; Muhammad Bilal Khan; Zhenli He; Hanumanth Kumar Gurajala; Xiaoe Yang (Journal of Soils and Sediments, 2019)

Genome wide characterization, evolution and expression analysis of FBA gene family under salt stress in Gossypium species - Muhammad Shehzad; Allah Ditta; Xiaoyan Cai; Zhongli Zhou; Xingxing Wang; Yanchao Xu; Yuqing Hou; Muhammad Yasir; Majid Khan; Kunbo Wang; Fang Liu (Biologia, 2019)

Assessing the solar PV power project site selection in Pakistan: based on AHP-fuzzy VIKOR approach - Yasir Ahmed Solangi; Syed Ahsan Ali Shah; Hashim Zameer; Muhammad Ikram; Burak Omer Saracoglu (Environmental Science and Pollution Research, 2019)

Evaluation of physiological markers for assessing drought tolerance and yield potential in bread wheat - Tauqeer Ahmad Yasir; Allah Wasaya; Mubshar Hussain; Muhammad Ijaz; Muhammad Farooq; Omer Farooq; Ahmad Nawaz; Yin-Gang Hu (Physiology and Molecular Biology of Plants, 2019)

Assessment of nematodes in Punjab Urial (Ovis vignei punjabiensis) population in Kalabagh Game Reserve: development of a DNA barcode approach - Amna Arshad Bajwa; Jordan Patrick Cuff; Muhammad Imran; Saher Islam; Riffat Mansha; Kamran Ashraf; Arman Khan; Muhammad Imran Rashid; Muhammad Yasir Zahoor; Waseem Ahmad Khan; Habib Ur Rehman; Asif Nadeem; et al. (European Journal of Wildlife Research, 2019)

Determinants of carbon emissions in Pakistan’s transport sector - Yasir Rasool; Syed Anees Haider Zaidi; Muhammad Wasif Zafar (Environmental Science and Pollution Research, 2019)

Assessing economic values of coral reefs in the Pangkajene and Kepulauan Regency, Spermonde Archipelago, Indonesia - La Ode Muhammad Yasir Haya; Masahiko Fujii (Journal of Coastal Conservation, 2019)

Anaerococcus jeddahensis sp. nov., a New Bacterial Species Isolated From Healthy Nomadic Bedouin Woman From Saudi Arabia - Niokhor Dione; Sara Bellali; Muhammad Yasir; Esam I. Azhar; Fehmida Bibi; Mamadou Beye; Nicholas Armstrong; Frédéric Cadoret; Asif A. Jiman-Fatani; Nayel Helmy; Jaishriram Rathored; Noémie Labas; et al. (Current Microbiology, 2018)

Accumulation of anthocyanin in callus cultures of red-pod okra [Abelmoschus esculentus (L.) Hongjiao] in response to light and nitrogen levels - Muhammad Irshad; Biswojit Debnath; Sangeeta Mitra; Yasir Arafat; Min Li; Yueting Sun; Dongliang Qiu (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Herausforderungen & Wichtigkeit der Korrosionsprüfung an automobilen Abgassystemanlagen - Simon Burger; Muhammad Yasir; Daniel Hornauer (BHM Berg- und Hüttenmännische Monatshefte, 2018)

Association of citrus leafminer Phyllocnistis citrella (Lepidoptera: Gracillariidae) damage with physiological parameters and larval weight in Citrus reticulata - Muhammad Arshad; Muhammad Irfan Ullah; Muhammad Afzal; Hafiz M. Aatif; Yasir Iftikhar; Jaime Molina-Ochoa; John E. Foster (International Journal of Tropical Insect Science, 2018)

Spatial analysis of precipitation time series over the Upper Indus Basin - Yasir Latif; Ma Yaoming; Muhammad Yaseen (Theoretical and Applied Climatology, 2018)

Nitrogen-regulated changes in total amino acid profile of maize genotypes having contrasting response to nitrogen deficit - Arshid Hussain Ganie; Altaf Ahmad; Peerzada Yasir Yousuf; Renu Pandey; Sayeed Ahmad; Ibrahim M Aref; Muhammad Iqbal (Protoplasma, 2017)

Mapping the change of coral reefs using remote sensing and in situ measurements: a case study in Pangkajene and Kepulauan Regency, Spermonde Archipelago, Indonesia - La Ode Muhammad Yasir Haya; Masahiko Fujii (Journal of Oceanography, 2017)

Osmopriming with CaCl2 improves wheat (Triticum aestivum L.) production under water-limited environments - Shahid Farooq; Mubshar Hussain; Khawar Jabran; Waseem Hassan; Muhammad S. Rizwan; Tauqeer A. Yasir (Environmental Science and Pollution Research, 2017)

Respiratory syncytial virus and influenza are the key viral pathogens in children <2 years hospitalized with bronchiolitis and pneumonia in Islamabad Pakistan - Uzma Bashir; Nadia Nisar; Yasir Arshad; Muhammad Masroor Alam; Asiya Ashraf; Hajra Sadia; Birjees Mazher Kazi; Syed Sohail Zahoor Zaidi (Archives of Virology, 2017)

Salt-stress-responsive chloroplast proteins in Brassica juncea genotypes with contrasting salt tolerance and their quantitative PCR analysis - Peerzada Yasir Yousuf; Altaf Ahmad; Ibrahim M. Aref; Munir Ozturk; Hemant; Arshid Hussain Ganie; Muhammad Iqbal (Protoplasma, 2016)

Association of tomato leaf curl Sudan virus with leaf curl disease of tomato in Jeddah, Saudi Arabia - Sayed Sartaj Sohrab; Muhammad Yasir; Sherif Ali El-Kafrawy; Ayman T. Abbas; Magdi Ali Ahmed Mousa; Ahmed A. Bakhashwain (VirusDisease, 2016)

Salt stress-induced modulations in the shoot proteome of Brassica juncea genotypes - Peerzada Yasir Yousuf; Altaf Ahmad; Arshid Hussain Ganie; Muhammad Iqbal (Environmental Science and Pollution Research, 2016)

Petrographic and structural controls on geotechnical feasibility of dam sites: implications from investigation at Sher Dara area (Swabi), north-western Pakistan - Yasir Shaheen Khalil; Mohammad Arif; Hasnain Ali Bangash; Muhammad Sajid; Noor Muhammad (Arabian Journal of Geosciences, 2015)

Impact of Condensates Containing Chloride and Sulphate on the Corrosion in Automotive Exhaust Systems - Reina Hashimoto; Gregor Mori; Muhammad Yasir; Uwe Tröger; Helmut Wieser (BHM Berg- und Hüttenmännische Monatshefte, 2013)

Growth promotion of cucumber by pure cultures of gibberellin-producing Phoma sp. GAH7 - Muhammad Hamayun; Sumera Afzal Khan; Abdul Latif Khan; Dong-Sheng Tang; Javid Hussain; Bashir Ahmad; Yasir Anwar; In-Jung Lee (World Journal of Microbiology and Biotechnology, 2010)